Thermal regime, isotopic and morphological characteristics of ice wedges in northern Victoria Land, Antarctica. - RAFFI, Rossana; B. STENNI; L. GENONI; O. FLORA; S. SEGA (U.S. GEOLOGICAL SURVEY AND THE NATIONAL ACADEMIES, 2007)
The preliminary results of the research carried out on six ice wedges located in the vicinity of Terra Nova Bay, in northern Victoria Land utilized co-isotope analyses to show that sublimation processes contribute to the formation of the ice-wedge ice. Analysis of the thermal regime of one ice wedge over a period of one year shows that extreme gradients between the ground surface and the top of the ice wedge temperatures may trigger ice-wedge cracking.